2004
DOI: 10.1016/j.ultrasmedbio.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurements of image quality

Abstract: Abstract:Tissue harmonic imaging (THI) and compound imaging have been reported clinically to improve contrast resolution, tissue differentiation and overall image quality.However, there have been limited studies to date to quantify objectively the improvements in image quality achieved with these new imaging techniques. The aim of this study was to quantify differences in image quality which exist between conventional Bmode imaging, harmonic imaging, compound imaging and harmonic compound imaging. An ATL HDI 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 18 publications
4
59
0
1
Order By: Relevance
“…An ex vivo subcutaneous pig fat layer was used to replicate beam distortion and phase aberration seen clinically in the presence of subcutaneous fat. Three different types of fat mimicking layers (olive oil, lard and lard with fish oil capsules) were evaluated.The subcutaneous pig fat layer demonstrated an improvement in anechoic target 3 detection with THI compared with 2D conventional imaging, but no improvement was demonstrated in contrast resolution performance; a similar result was found in a previous study conducted by this research group (Browne et al 2004) while using this tissue mimicking phantom without a fat layer. Similarly, while using the layers of olive oil, lard and lard with fish oil capsules, improvements due to THI were found in anechoic target detection but, again, no improvements were found for contrast resolution for any of the layer combinations.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…An ex vivo subcutaneous pig fat layer was used to replicate beam distortion and phase aberration seen clinically in the presence of subcutaneous fat. Three different types of fat mimicking layers (olive oil, lard and lard with fish oil capsules) were evaluated.The subcutaneous pig fat layer demonstrated an improvement in anechoic target 3 detection with THI compared with 2D conventional imaging, but no improvement was demonstrated in contrast resolution performance; a similar result was found in a previous study conducted by this research group (Browne et al 2004) while using this tissue mimicking phantom without a fat layer. Similarly, while using the layers of olive oil, lard and lard with fish oil capsules, improvements due to THI were found in anechoic target detection but, again, no improvements were found for contrast resolution for any of the layer combinations.…”
supporting
confidence: 84%
“…However, a study carried out previously by the authors (Browne et al 2004) found improvements only in spatial resolution and not in contrast resolution or anechoic target detection.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…There are many methods and recommendations on how to carry out performance tests and quality control on ultrasound systems 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. The transducer is a vital part of the system and handled daily.…”
Section: Introductionmentioning
confidence: 99%